A ceramic metal seal structure for inhibiting copper solder erosion and a preparation process thereof
Patent Information
- Application Number
- CN202611189461.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种抑制铜焊料熔蚀的陶瓷金属封接结构及其制备工艺,以解决在纯铜高温钎焊工况下,常规薄Ni层极易被液态铜完全溶解,导致底层Mo-Mn金属化层失去保护而被液态纯铜熔蚀,进而引发封接界面漏气、结合强度下降及可靠性失效的技术问题
本发明公开的一种抑制铜焊料熔蚀的陶瓷金属封接结构,包括:氧化铝陶瓷件、Mo-Mn基础金属化层和Ni层三层基础结构,Ni层在厚度方向上分为内侧致密Ni层和外侧疏松Ni层,外侧疏松层作为牺牲层优先与液态纯铜反应消耗、内侧致密层经高温预扩散与Mo-Mn基础金属化层形成Ni-Mo冶金结合层后作为物理屏障阻挡铜液渗透,实现了外层主动消耗与内层被动防御的协同配合。从根本上切断了液态纯铜对Mo-Mn基础金属化层的熔蚀通道,高温钎焊时,外侧疏松Ni层因结构粗大、晶界丰富,优先被液态铜溶解并进入铜液,该过程既消耗了侵蚀性介质液态铜的攻击力,又改善了纯铜钎料的润湿铺展性;残余液态铜到达内侧致密Ni层时,因该层已通过预扩散形成高熔点、高致密的Ni-Mo冶金结合层,且镍在液态铜中的溶解度有限,在短暂的钎焊保温时间内无法完全溶解厚度达2~5μm的致密镍层,从而被有效截留。表1和表2的实验数据有力支撑了上述机理分析:1#实施例封接后内侧残余致密Ni层完好保留(4.9μm),抗拉强度达375.5MPa,氦漏率达1×10-13Pa·m3/s;而2#对比例(未预扩散)镍层被完全熔蚀(0μm),抗拉强度仅246.9MPa;3#对比例(无疏松层)镍层亦被完全熔蚀,抗拉强度仅233.9MPa;4#对比例(既无疏松层又未预扩散)钼层厚度从18.7μm减薄至10.2μm,表明金属化层已被严重侵蚀,抗拉强度仅123.6MPa,漏率劣化至10-6Pa·m3/s。本发明通过双层结构与高温预扩散协同作用的完整方案,实现纯铜高温钎焊的有效防护。
Smart Images

Figure CN122977873A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the interdisciplinary technical field of manufacturing electronic vacuum devices and medical X-ray equipment, specifically relating to a ceramic-metal sealing structure for inhibiting copper solder erosion and its preparation process. Background Technology
[0002] Ceramic-metal sealing assemblies are key components in the cathode insulator, anode insulator, and high-voltage insulation structure of CT X-ray tubes. Their sealing interfaces must simultaneously meet requirements for vacuum tightness, high dielectric strength, mechanical strength, and thermal cycling reliability. Conventional ceramic-metal sealing often employs alumina ceramic Mo-Mn metallization, surface Ni plating, or Ag-Cu type brazing with vacuum or protective atmosphere brazing. The working mechanism of a CT X-ray tube is as follows: after the cathode filament is heated by electricity, it releases electrons, which bombard the anode target surface at high speed under the action of a high-voltage electric field. Only about 1% of the energy is converted into X-rays and output through the window, while the remaining approximately 99% is released as heat. This results in the ceramic-metal sealing assemblies used in CT X-ray tubes operating at high temperatures of approximately 400℃ to 600℃ during long-term operation. Since AgCu28 solder has a melting point of only 792℃, within the aforementioned temperature range, long-term service of AgCu28 solder will result in significant creep, rapid stress relaxation, rapid coarsening of the eutectic structure, and accelerated interface diffusion. This will directly lead to a decrease in the airtightness and strength of the joint over time. Based on these service failure risks, using pure copper or oxygen-free copper with higher melting points as brazing materials can improve the creep resistance of the joint and adapt it to high-temperature vacuum service environments. However, the brazing temperature of pure copper is usually close to or higher than 1083℃, significantly increasing the risk of corrosion of the conventional Mo-Mn metallization layer and its thin Ni layer by liquid copper.
[0003] In conventional processes, a thin Ni layer is typically deposited on the surface of the Mo-Mn metallization layer to improve wetting and act as a diffusion barrier. However, during high-temperature brazing of pure copper, the thin Ni layer may be rapidly dissolved by the molten copper during the holding phase, leading to direct contact and erosion of the Mo-Mn metallization layer by the molten copper. This results in problems such as discontinuous interface layer, voids, peeling, gas leakage, and reduced strength. Existing mitigation solutions often involve alloying the solder, such as changing the composition of Ag-Cu, Cu-Ti, Cu-Pd, or other active / noble metal solders. However, this approach introduces issues related to cost, material systems, vacuum venting, and process compatibility. Chinese patent application CN108161274B discloses a silver-based sealing solder for electro-vacuum devices. It improves solder performance and reduces silver content by adding Ni, Ti, and In elements to Ag-Cu solder. However, it still belongs to a medium-temperature solder system (melting point approximately 757~793℃), which cannot meet the long-term thermal stability requirements of brazed joints under the high-temperature service conditions of CT X-ray tubes. Furthermore, its technical approach involves changing the solder composition. Chinese patent application CN115974575B discloses a method for preparing a ceramic-metal packaged connector, employing a process route of Mo-Mn metallization, electroplating a 4~5μm nickel layer, and brazing Ag72Cu28 eutectic solder at 850~920℃. However, it also remains within the medium-temperature AgCu28 solder system, and its nickel layer is only a conventional single thin layer. It does not address the erosion problem of the Mo-Mn metallization layer by liquid copper in high-temperature pure copper brazing and the corresponding interface barrier solution. The aforementioned existing technologies have failed to solve the technical problem of severe erosion of the Mo-Mn metallization layer by liquid copper during high-temperature brazing of pure copper. In conventional processes, the thin Ni layer on the surface of the Mo-Mn metallization layer is easily dissolved by liquid copper during high-temperature brazing of pure copper (≥1083℃), causing the liquid copper to directly contact and erode the Mo-Mn metallization layer, resulting in a series of problems such as discontinuous interface layer, voids, peeling, air leakage, and reduced strength.
[0004] Therefore, there is an urgent need to find a pure copper brazed ceramic-metal sealing assembly and its preparation method suitable for the high-temperature vacuum conditions of CT tubes. This study chooses to maintain the pure copper brazing filler metal system and addresses the erosion problem from the perspectives of interface structure and process control. Without changing the filler metal composition, a double-layered thickened Ni barrier layer is constructed, consisting of an inner dense and an outer loose layer, supplemented by high-temperature pre-diffusion densification treatment. The outer loose nickel layer acts as a sacrificial layer, preferentially reacting with and consuming the liquid copper, while the inner dense nickel layer, after pre-diffusion, forms a Ni-Mo metallurgical bonding physical barrier. This synergistic effect effectively prevents the pure copper solder from penetrating the Ni layer and directly eroding the Mo-Mn metallization layer during high-temperature sealing, thereby ensuring the hermeticity, high bonding strength, and thermal cycling stability of the ceramic-metal interface. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a ceramic-metal sealing structure and its preparation process for inhibiting copper solder erosion, so as to solve the technical problem that under the high temperature brazing condition of pure copper, the conventional thin Ni layer is easily completely dissolved by liquid copper, which causes the underlying Mo-Mn metallization layer to lose protection and be eroded by liquid pure copper, thereby causing leakage at the sealing interface, reduced bonding strength and reliability failure.
[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a ceramic-metal sealing structure for inhibiting copper solder erosion, comprising: Alumina ceramic parts; A Mo-Mn-based metallization layer is formed on the surface of the area to be sealed in the alumina ceramic part; A Ni layer formed on the surface of a Mo-Mn-based metallized layer; The Ni layer is divided into a dense Ni layer on the inside and a loose Ni layer on the outside in the thickness direction. A Ni-Mo metallurgical bonding layer is formed between the dense Ni layer and the Mo-Mn basic metallization layer through high-temperature pre-diffusion treatment; The loose Ni layer on the outside is used as a sacrificial layer to preferentially react with liquid pure copper and be consumed during the high-temperature brazing of pure copper. The dense Ni layer on the inside acts as a physical barrier to prevent liquid pure copper from penetrating into the Mo-Mn base metallization layer after the loose Ni layer on the outside is consumed.
[0007] Preferably, the total thickness of the Ni layer is 7~20μm; the thickness of the dense Ni layer is 2~5μm; and the thickness of the porous Ni layer is 5~15μm.
[0008] Preferably, the alumina ceramic component is selected from 95% alumina ceramic, 96% alumina ceramic, 99% alumina ceramic, 99.5% alumina ceramic or 99.7% alumina ceramic.
[0009] Preferably, the thickness of the Mo-Mn base metallization layer is 15~25μm.
[0010] Preferably, oxygen-free copper TU0, TU1 or TU2 is used as the brazing material for pure copper brazing, and the brazing temperature for pure copper brazing is 1130~1180℃.
[0011] This invention also discloses a process for preparing a ceramic-metal sealing structure that inhibits copper solder erosion, comprising the following steps: A Mo-Mn-based metallization layer is prepared on the surface of the area to be sealed in an alumina ceramic part; A Ni layer is prepared on the surface of a Mo-Mn-based metallized layer. The Ni layer is divided into a dense Ni layer on the inner side and a loose Ni layer on the outer side in the thickness direction. The alumina ceramic part with the Ni layer was placed in a reducing atmosphere furnace for high-temperature pre-diffusion treatment, so that a Ni-Mo metallurgical bonding layer was formed between the dense Ni layer and the Mo-Mn basic metallization layer. After the pre-diffusion treated alumina ceramic parts, pure copper brazing filler metal and metal parts are assembled in a set order, they are then subjected to high-temperature vacuum brazing. During the brazing process, the loose Ni layer on the outside acts as a sacrificial layer and is preferentially consumed by reacting with liquid pure copper, while the dense Ni layer on the inside acts as a physical barrier to prevent liquid pure copper from penetrating into the Mo-Mn base metallization layer.
[0012] Preferably, the Ni layer is prepared by any one of electroplating, electroless plating, physical vapor deposition, or composite deposition.
[0013] More preferably, when using the Ni electroplating process, a two-stage variable current method is employed, specifically including: First-stage electroplating: control the electroplating current density to be 0.5~1.5A / dm² 2 The electroplating time is 15~30min to form a dense Ni layer on the inner side, with a thickness controlled at 2~5μm; Second-stage electroplating: Control the electroplating current density to increase to 4.0~8.0 A / dm² 2 The electroplating time is 3~10min, forming a loose Ni layer on the outer side on the surface of the dense Ni layer on the inner side, with a thickness controlled at 5~15μm.
[0014] Preferably, the high-temperature pre-diffusion treatment is carried out at a temperature of 750~1050℃ for 20~45min; the reducing atmosphere furnace is a hydrogen furnace or an ammonia decomposition furnace.
[0015] Preferably, the high-temperature vacuum brazing temperature is 1130~1180℃, the holding time is 3~20min, and the vacuum degree is below 10. -3 Pa; the pure copper brazing filler metal is selected from oxygen-free copper TU0, TU1 or TU2; the material of the metal parts is selected from any one of Kovar alloy 4J29, Kovar alloy 4J33, Fe-Ni-Co alloy, Fe-Ni alloy, Hastelloy alloy and stainless steel parts with Ni surface plating.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a ceramic-metal sealing structure for inhibiting copper solder erosion, comprising a three-layer basic structure: an alumina ceramic component, a Mo-Mn base metallization layer, and a Ni layer. The Ni layer is divided into an inner dense Ni layer and an outer loose Ni layer in the thickness direction. The outer loose layer acts as a sacrificial layer and preferentially reacts with liquid pure copper for consumption. The inner dense layer, after high-temperature pre-diffusion, forms a Ni-Mo metallurgical bonding layer with the Mo-Mn base metallization layer, which then acts as a physical barrier to prevent copper liquid penetration. This achieves a synergistic cooperation between the active consumption of the outer layer and the passive defense of the inner layer. This process fundamentally cuts off the erosion channel of liquid pure copper on the Mo-Mn base metallization layer. During high-temperature brazing, the outer porous Ni layer, due to its coarse structure and abundant grain boundaries, is preferentially dissolved by the liquid copper and enters the copper melt. This process not only consumes the attacking force of the corrosive medium liquid copper but also improves the wetting and spreading properties of the pure copper brazing filler metal. When the residual liquid copper reaches the inner dense Ni layer, it is effectively trapped because this layer has already formed a high-melting-point, highly dense Ni-Mo metallurgical bonding layer through pre-diffusion, and the solubility of nickel in liquid copper is limited. Therefore, it cannot completely dissolve the dense nickel layer with a thickness of 2-5 μm within the short brazing holding time. The experimental data in Tables 1 and 2 strongly support the above mechanism analysis: In Example 1, the inner residual dense Ni layer was intact after sealing (4.9 μm), with a tensile strength of 375.5 MPa and a helium leakage rate of 1×10⁻⁶. -13 Pa·m 3 / s; while in comparative example #2 (without pre-diffusion), the nickel layer was completely eroded (0 μm), with a tensile strength of only 246.9 MPa; in comparative example #3 (without a porous layer), the nickel layer was also completely eroded, with a tensile strength of only 233.9 MPa; in comparative example #4 (without a porous layer and without pre-diffusion), the molybdenum layer thickness decreased from 18.7 μm to 10.2 μm, indicating that the metallization layer had been severely eroded, with a tensile strength of only 123.6 MPa and a leakage rate deterioration to 10. -6 Pa·m 3 This invention achieves effective protection for high-temperature brazing of pure copper through a complete solution combining a double-layer structure and high-temperature pre-diffusion.
[0017] This invention discloses a process for fabricating a ceramic-metal sealing structure that inhibits copper solder erosion. The process includes preparing a Mo-Mn base metallization layer and a Ni layer, high-temperature pre-diffusion treatment, and high-temperature vacuum brazing. Before brazing and after the double Ni layer is prepared, the component is placed in a reducing atmosphere furnace for heat treatment. The high temperature promotes sufficient solid-state interdiffusion between Ni atoms in the inner dense Ni layer and Mo atoms in the bottom Mo-Mn metallization layer, forming a Ni-Mo metallurgical bonding layer. The melting point of this metallurgical bonding region is much higher than the brazing temperature of pure copper, thus enabling it to resist the dissolution and erosion of liquid copper in a chemically stable manner during brazing. Furthermore, the high-temperature treatment eliminates the unavoidable micropores and lattice defects during the electroplating process of the inner dense Ni layer, transforming the originally electrodeposited Ni layer into a highly dense metallurgical layer, significantly improving its physical barrier properties. The key difference between Comparative Example 1 (sample #2) and Example #1 lies solely in whether or not it underwent pre-diffusion treatment. Sample #2 did not undergo pre-diffusion treatment. Although it had a double-layer Ni layer of the same thickness as #1, the entire Ni layer was completely melted by liquid copper after brazing (residual thickness 0 μm), resulting in a tensile strength of only 246.9 MPa and a leakage rate deterioration to 10. -9 Pa·m 3 The sample size was on the order of / s; while the pre-diffusion treated sample #1 not only retained a dense Ni layer intact (residual thickness 4.9μm), but also achieved a tensile strength of 375.5MPa and a leakage rate stable at 10. -13 Pa·m 3 This process route avoids the increased costs caused by changing the solder composition, the long development cycle of new solder formulations, and the compatibility issues such as the degradation of joint performance due to accelerated grain boundary diffusion of Ag elements in silver-copper solders such as AgCu28 under long-term high-temperature service. It provides a complete, controllable, and repeatable process route for the engineering application of pure copper solders in ceramic-metal sealing of high-temperature electro-vacuum devices such as CT X-ray tubes. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the ceramic-metal sealing structure for inhibiting copper solder erosion according to the present invention; Figure 2 Images of insulating ceramic-sealed leads for CT tubes produced for this invention; wherein, (a) is the overall appearance of the lead assembly; (b) is the composite brazing interface of the ceramic end face flat seal and the pin seal; and (c) is the end face of the lead pin hole sealing side. Figure 3 This is a schematic diagram of the fracture modes of tensile test samples No. 1 and No. 5 of this invention.
[0019] Among them, 1. Alumina ceramic body; 2. Mo-Mn basic metallization layer; 3. Ni-Mo metallurgical bonding layer; 4. Dense Ni layer; 5. Loose Ni layer; 6. Ni layer. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.
[0022] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.
[0023] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.
[0024] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.
[0025] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.
[0026] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.
[0027] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.
[0028] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.
[0029] This invention specifically relates to a ceramic-metal sealing structure and its preparation process for inhibiting copper solder erosion, used in CT tubes and X-ray tubes. More specifically, this invention relates to an interface barrier structure and process control method for preventing liquid copper from eroding the Mo-Mn basic metallization layer 2 on the surface of an alumina ceramic part 1 during high-temperature hermetically sealed bonding using pure copper or oxygen-free copper as brazing filler material, thereby avoiding sealing failure between the alumina ceramic part 1 and metal parts (such as Kovar alloy, Fe-Ni-Co alloy, Fe-Ni alloy, Hastelloy, or stainless steel).
[0030] This invention does not aim to change the composition of the brazing filler metal, nor does it involve the research and development of silver-copper brazing filler metal, active brazing filler metal, or precious metal brazing filler metal formulations. Instead, it solves the problem of metallization layer erosion in high-temperature brazing of pure copper by using a dense barrier layer above the ceramic metallization layer.
[0031] The present invention aims to effectively prevent pure copper solder from penetrating the Ni layer and directly melting the Mo-Mn base metallization layer 2 during the high-temperature sealing process by constructing a Ni barrier layer with a specific structure, thereby ensuring the airtightness, high bonding strength and excellent thermal cycling stability of the ceramic-metal interface.
[0032] The core technical problem that this invention aims to solve is that under the condition of high-temperature brazing of pure copper, the conventional thin Ni layer is easily completely dissolved by liquid copper, causing the underlying Mo-Mn metallization layer 2 to lose protection and be eroded by liquid pure copper, which in turn leads to problems such as leakage at the sealing interface, reduced bonding strength and reliability failure.
[0033] The basic idea of this invention is to employ a thickened nickel layer design with a "dense inner layer and loose outer layer" dual-layer structure to effectively prevent the erosion of pure copper solder. The specific technical solution is as follows: 1) Constructing a double-layer thickened structure: A thickened high-quality Ni layer 6 is prepared on the surface of the Mo-Mn base metallization layer 2. The thickened Ni layer 6 is divided into an outermost loose Ni layer 5 and an inner dense Ni layer 4 in the thickness direction.
[0034] 2) Outer layer sacrificial reaction mechanism: The outermost loose Ni layer 5 acts as a sacrificial layer. During the high-temperature process of pure copper sealing, it preferentially and fully reacts with the liquid copper solder and is consumed, thereby delaying and buffering the process of liquid copper erosion inward.
[0035] 3) Inner layer pre-diffusion barrier mechanism: The dense Ni layer 4 undergoes a specialized high-temperature pretreatment process to achieve deep diffusion with the underlying Mo-Mn base metallization layer 2 and form a robust Ni-Mo metallurgical bonding layer 3. During actual brazing, the dense Ni layer 4 and the Ni-Mo metallurgical bonding layer 3 act as a strong physical barrier, effectively preventing further penetration of liquid copper and completely cutting off the erosion channel of liquid copper to the Mo-Mn base metallization layer 2, thereby ensuring the sealing quality.
[0036] The present invention discloses a ceramic-metal sealing structure for inhibiting copper solder erosion, comprising: an alumina ceramic component 1, a Mo-Mn basic metallization layer 2 formed on the surface of the area to be sealed of the alumina ceramic component 1, and a thickened Ni layer 6 formed on the surface of the Mo-Mn basic metallization layer 2.
[0037] The thickness of the thickened Ni layer 6 is 7~20μm. Before brazing, the thickened Ni layer 6 undergoes a pre-diffusion treatment at 850~950℃. Its inner side reacts with the Mo-Mn base metallization layer 2 to form a dense Ni-Mo metallurgical bonding layer 3. Its outer side is a relatively loose sacrificial layer.
[0038] After high-temperature brazing with pure copper, the loose outer portion of the thickened Ni layer 6 is dissolved by the liquid pure copper, forming a Cu-Ni transition region; while a continuous residual dense Ni barrier layer remains on the side near the Mo-Mn base metallization layer 2. The residual dense Ni barrier layer cuts off the erosion channel of the copper liquid, preventing the copper liquid from directly contacting and eroding the Mo-Mn base metallization layer 2.
[0039] Preferably, the metal parts sealed to the ceramic parts by pure copper solder are made of Kovar alloy (such as 4J29, 4J33), Fe-Ni-Co alloy, Fe-Ni alloy, Hastelloy alloy, or stainless steel parts with Ni-plated surface treatment.
[0040] Experimental steps: 1. Ceramic metallization Weigh out dry powder containing 80% Mo powder, 10% Mn powder, and 10% glass powder (the glass powder composition is 50% Al2O3, 30% SiO2, and 20% MgO by mass). Weigh out terpineol, which accounts for 25% of the weight of the dry powder. Mix the dry powder and terpineol in a porcelain jar, add agate balls accounting for 80% of the total weight of the dry powder and terpineol, and grind in a planetary grinder for 12 hours to prepare Mo-Mn metallizing paste.
[0041] Select 95%, 96%, 99%, 99.5% or 99.7% alumina ceramics, or other oxide ceramics suitable for Mo-Mn metallization, and apply Mo-Mn metallization paste to the ceramic sealing area by screen printing or hand coating. Then, sinter at a high temperature of 1300~1500℃ under a humid hydrogen atmosphere to form a Mo-Mn basic metallization layer 2 with a thickness of 15~25μm.
[0042] 2. Preparation of a double-layer thickened Ni barrier layer A thickened Ni layer 6 with a double-layer structure is deposited on the surface of the Mo-Mn base metallization layer 2. The Ni layer 6 can be formed by electroplating, electroless plating, physical vapor deposition (PVD), or composite deposition. To reduce the risk of gas release from the CT tube under high-temperature vacuum conditions and to ensure the purity of the coating, this invention preferably uses an electroplating Ni process. This electroplating process employs a two-stage variable current method, and the specific steps are as follows: First-stage electroplating (construction of the inner dense layer): A first Ni layer is applied on the Mo-Mn base metallization layer using a low current density and long processing time. The electroplating current density is controlled at 0.5~1.5 A / dm³. 2 The electroplating time is 15-30 min, and the thickness of the resulting dense Ni layer is controlled at 2-5 μm. Under this low current density condition, the deposition rate is slow, and the nucleation rate of nickel grains is higher than the growth rate, thus forming a highly dense basic Ni layer with fine crystals and extremely low porosity.
[0043] Second-stage electroplating (construction of the outer porous layer): A high current density combined with a short processing time is then used to apply a second Ni layer onto the surface of the first Ni layer. The electroplating current density is controlled to increase to 4.0~8.0 A / dm². 2 The electroplating time is 3-10 min, and the thickness of the resulting outer Ni layer is controlled at 5-15 μm. Under this high current density condition, the deposition rate increases dramatically, accompanied by a slight hydrogen evolution side reaction, resulting in coarse nickel grains and a relatively loose coating structure, thus precisely constructing a sacrificial layer that preferentially reacts with liquid pure copper during brazing.
[0044] High-temperature pre-diffusion densification treatment: The alumina ceramic part 1 after double-stage nickel electroplating is placed in a reducing atmosphere furnace (such as a hydrogen furnace or ammonia decomposition furnace) and heat-treated at 750~1050℃ (preferably 850~950℃) for 20~45 minutes. The purpose of this step is to: utilize high temperature to promote elemental interdiffusion between Ni and the underlying Mo-Mn base metallization layer 2, further eliminate the micropores of the inner electroplated Ni layer, and significantly improve its density; at the same time, a deep Ni-Mo metallurgical bonding layer 3 is formed at the interface between the Ni layer 6 and the Mo-Mn base metallization layer 2, establishing a solid underlying physical barrier to prevent subsequent melting of liquid pure copper.
[0045] 3. Sealing and assembly The alumina ceramic component 1, which has undergone Mo-Mn metallization and double-layer thickened Ni plating, pure copper brazing filler metal (material selected from oxygen-free copper TU0, TU1, or TU2, preferably TU1), and metal structural components (selected from 4J33 or 4J29 Kovar alloy, etc.) are precisely assembled in a predetermined sequence. During assembly, ensure that the pure copper brazing filler metal is accurately clamped between the thickened Ni layer 6 of the ceramic component and the sealing surface of the metal structural component, and apply an appropriate assembly preload force using a clamp.
[0046] 4. High-temperature vacuum brazing The assembled components are placed in a vacuum furnace for high-temperature brazing. The vacuum level inside the furnace, whether cold or hot, must be controlled below 10. -3Pa. Heat to 1130~1180℃ according to the set heating curve, and keep warm for 3~20 minutes (Note: The specific holding time can be adjusted flexibly according to the volume and heat capacity of the sealing component, preferably 3~15 minutes).
[0047] During this high-temperature brazing and pure copper melting process, the loose Ni layer 5 (approximately 5-15 μm thick) on the outer side of the thickened Ni layer 6 acts as a sacrificial layer, preferentially and rapidly dissolving into the liquid pure copper. This process effectively improves the wettability and spreading performance of the pure copper brazing filler metal. Meanwhile, the dense Ni layer 4 (approximately 2-5 μm thick) on the inner side, having undergone high-temperature pre-diffusion treatment, forms a robust Ni-Mo metallurgical bonding layer 3 with a highly dense structure. This layer successfully resists the penetration of liquid pure copper, completely blocking the channel for the molten copper to directly contact and erode the underlying Mo-Mn base metallization layer 2 (i.e., acting as a physical barrier layer), thereby ensuring the high strength and airtightness of the ceramic-metal interface.
[0048] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0049] Experimental Results: 1. A total of 5 groups of samples were prepared according to the experimental grouping scheme, as shown in Table 1: Table 1. Comparison of experimental conditions for ceramic-metal sealing structures prepared in the examples and comparative examples.
[0050] 2. Experimental Procedure Example 1 The Mo-Mn metallizing paste was prepared according to the above experimental steps; the Mo-Mn metallizing paste was applied to the sealing area of the ceramic part by screen printing; the sample coated with the Mo-Mn metallizing paste was sintered in a wet hydrogen atmosphere furnace at 1450℃, and the actual thickness of the Mo layer after sintering was measured to be 18.3 μm using an X-ray thickness gauge; the electroplating current density was controlled at 1 A / dm³. 2 Electroplating for 25 minutes resulted in a dense Ni layer with a measured thickness of 2.5 μm; the electroplating current density was controlled at 8.0 A / dm³. 2The electroplating time was 3 min, and the actual thickness of the resulting loose Ni layer 5 was 7.7 μm. The electroplated ceramic parts were pre-diffusion sintered at 950 °C for 30 min in a dry hydrogen atmosphere furnace. The sintered samples were then sealed with Kovar metal parts using TU1 pure copper solder and held at 1180 °C for 10 min in a dry hydrogen atmosphere furnace.
[0051] Example 2 The Mo-Mn metallization paste was prepared according to the steps in Example 1 and screen-printed onto the 96% alumina ceramic surface to be sealed. It was then sintered at 1450°C in a humid hydrogen atmosphere to obtain a 15 μm thick Mo-Mn base metallization layer 2. Ni plating was performed using a two-stage variable current electroplating method: First stage: current density 0.5 A / dm³. 2 The time was 15 min, forming a dense Ni layer with a thickness of 2 μm; the second stage: current density 4.0 A / dm. 2 The process takes 10 minutes to form a loose Ni layer with a thickness of 5 μm (total Ni layer thickness 7 μm). After electroplating, the plated plate is placed in an ammonia decomposition atmosphere furnace and pre-diffused at 750 °C for 20 minutes. It is then assembled with TU0 pure copper solder and Fe-Ni-Co alloy parts under a vacuum degree <10 -3 The temperature was raised to 1130 ℃ under Pa and held for 3 minutes to complete the brazing.
[0052] Example 3 99% alumina ceramic was selected, and the thickness of the Mo-Mn base metallization layer 2 after sintering was 25 μm. Ni electroplating: First stage: 1.5 A / dm 2 30 min, dense Ni layer 4, thickness 5 μm; second stage: 6.0 A / dm 2 The process involved 6 min of pre-diffusion, resulting in a loose Ni layer 5 with a thickness of 15 μm (total thickness 20 μm). Pre-diffusion was performed in a hydrogen atmosphere at 1050 °C for 45 min. Brazing was then performed using TU2 pure copper solder with Fe-Ni alloy parts at 1150 °C for 20 min, with a vacuum degree <10. -3 Pa.
[0053] Example 4 99.5% alumina ceramic was selected, and the thickness of the Mo-Mn base metallization layer 2 was 20 μm. Electroplating: First stage: 1.2 A / dm 2 , 20 min, dense Ni layer 4, thickness 3 μm; second stage: 5.0 A / dm 2 7 min, loose Ni layer 5 thickness 9 μm (total thickness 12 μm). Pre-diffusion in hydrogen atmosphere, 850 ℃ for 30 min. Brazing using TU0 pure copper solder with Hastelloy parts, brazing temperature 1160 ℃, holding for 15 min, vacuum degree <10 -3 Pa.
[0054] Example 5 99.7% alumina ceramic was selected, and the thickness of the Mo-Mn base metallization layer 2 was 22 μm. Electroplating: First stage: 0.8 A / dm 2 , 18 min, dense Ni layer 4, thickness 4 μm; second stage: 7.0 A / dm 2 8 min, loose Ni layer 5, thickness 11 μm (total thickness 15 μm). Pre-diffusion in hydrogen atmosphere, 900 ℃ for 35 min. Brazing using TU2 pure copper solder to Ni-plated stainless steel parts, brazing temperature 1170 ℃, holding for 5 min, vacuum degree <10 -3 Pa.
[0055] Comparative Example 1 The Mo-Mn metallizing paste was prepared according to the above experimental steps; the Mo-Mn metallizing paste was applied to the sealing area of the ceramic part by screen printing; the sample coated with Mo-Mn metallizing paste was sintered in a wet hydrogen atmosphere furnace at 1450℃, and the actual thickness of the Mo layer after sintering was measured to be 17.9 μm using an X-ray thickness gauge; the electroplating current density was controlled at 1 A / dm³. 2 Electroplating for 30 minutes resulted in a dense Ni layer with a measured thickness of 2.7 μm; the electroplating current density was controlled at 8.0 A / dm³. 2 The electroplating time was 5 minutes, and the actual thickness of the resulting loose Ni layer 5 was 8.1 μm. After electroplating, the ceramic parts were sealed with Kovar metal parts in a dry hydrogen atmosphere furnace at 1180℃ for 10 minutes using TU1 pure copper solder.
[0056] Comparative Example 2 The Mo-Mn metallizing paste was prepared according to the above experimental steps; the Mo-Mn metallizing paste was applied to the sealing area of the ceramic part by screen printing; the sample coated with Mo-Mn metallizing paste was sintered in a wet hydrogen atmosphere furnace at 1450℃, and the actual thickness of the Mo layer after sintering was measured to be 19.8 μm using an X-ray thickness gauge; the electroplating current density was controlled at 1 A / dm³. 2 Electroplating for 20 minutes resulted in a dense Ni layer with a measured thickness of 2.3 μm. The electroplated ceramic parts were then pre-diffusion sintered at 950°C for 30 minutes in a dry hydrogen atmosphere furnace. The sintered ceramic parts were then sealed with Kovar metal parts using TU1 pure copper solder at 1180°C for 10 minutes in a dry hydrogen atmosphere furnace.
[0057] Comparative Example 3 The Mo-Mn metallizing paste was prepared according to the above experimental steps; the Mo-Mn metallizing paste was applied to the sealing area of the ceramic part by screen printing; the sample coated with the Mo-Mn metallizing paste was sintered in a wet hydrogen atmosphere furnace at 1450℃, and the actual thickness of the Mo layer after sintering was measured to be 18.7 μm using an X-ray thickness gauge; the electroplating current density was controlled at 1 A / dm³. 2 Electroplating for 20 minutes resulted in a dense Ni layer with a measured thickness of 2.1 μm. The electroplated ceramic parts were then sealed with Kovar metal parts in a dry hydrogen atmosphere furnace at 1180°C for 10 minutes using TU1 pure copper solder.
[0058] Existing technology benchmark group The Mo-Mn metallizing paste was prepared according to the above experimental steps; the Mo-Mn metallizing paste was applied to the sealing area of the ceramic part by screen printing; the sample coated with the Mo-Mn metallizing paste was sintered in a wet hydrogen atmosphere furnace at 1450℃, and the actual thickness of the Mo layer after sintering was measured to be 16.2 μm using an X-ray thickness gauge; the electroplating current density was controlled at 1 A / dm³. 2 Electroplating for 30 minutes resulted in a dense Ni layer with a measured thickness of 2.7 μm. The electroplated ceramic parts were then sealed with Kovar metal parts using AgCu28 solder in a dry hydrogen atmosphere furnace at 820°C for 10 minutes.
[0059] Figure 1 This is a schematic diagram of the ceramic-metal sealing structure for inhibiting copper solder erosion according to the present invention. As can be seen from the figure, the present invention applies a double-layer thickened Ni layer 6 on the Mo-Mn base metallization layer 2: a dense Ni layer 4 and a loose Ni layer 5. The micropores and lattice defects in the dense Ni layer 4 are eliminated by high-temperature pre-diffusion treatment, and the dense Ni layer 4 and the Mo-Mn base metallization layer 2 are formed by high-temperature pre-diffusion to form a Ni-Mo metallurgical bonding layer 3. The melting point of this metallurgical bonding zone is much higher than the brazing temperature of pure copper, so that it can resist the dissolution and erosion of liquid copper in a chemically stable manner during brazing.
[0060] Figure 2 Images of the insulating ceramic-sealed lead wire for CT tubes produced according to this invention are shown. (a) shows the overall appearance of the lead wire assembly; (b) shows the composite brazing interface of the ceramic end face flat seal and pin seal; (c) shows the pinhole sealing side end face of the lead wire. This product, manufactured by Baoguang Ceramics Technology Co., Ltd., uses copper solder for sealing. Its model number is DK.14124, and its product name is insulating ceramic-sealed lead wire. It is one of the components used in assembling CT tubes. As can be seen from the images, this product integrates several typical complex sealing methods, specifically including: 1) a sleeve seal between the alumina ceramic component 1 and the Kovar alloy component (sleeve seal); 2) a pinhole seal between the Kovar alloy component and the nickel pin (pin seal); and 3) a flat seal between the alumina ceramic component 1 and the Kovar alloy component (flat seal).
[0061] Figure 3 This diagram illustrates the fracture modes of samples #1 and #5 in the tensile test of this invention. As can be seen from the diagram, the tensile fracture locations of both the #1 pure copper solder example and the prior art benchmark group #5 occurred within the ceramic matrix near the interface (i.e., a typical "pulling out" phenomenon / white porcelain area). This failure mode indicates that the metallurgical bonding strength of the ceramic-metal interface exceeds the cohesive fracture strength of 95% alumina ceramic material itself, fully demonstrating that the sealing assembly of this invention possesses extremely superior and reliable interface connection quality.
[0062] 3. Performance Testing Methods Preparation of specimens for tensile strength testing: 95% alumina ceramic was selected as the substrate. After Mo-Mn basic metallization was completed by applying metallization paste to its surface, nickel plating and corresponding pre-diffusion heat treatment were carried out strictly according to the set parameters of each group in Table 1 above. Subsequently, the ceramic was cut and processed into ceramic test columns with a metallized end face size of 5×15mm and a height of 10mm.
[0063] Tensile strength test method: The ceramic test column prepared above was assembled and sealed with a Φ3mm Kovar alloy (4J29 / 4J33) rod using TU1 oxygen-free copper solder sheet or AgCu28 silver-copper solder sheet with a thickness of 0.1 mm. After sealing, the tensile strength of the ceramic-metal interface of each group of samples was tested on a universal testing machine, and the fracture load and fracture morphology were recorded.
[0064] Air tightness (leakage rate) test: Based on the actual application conditions of this invention, the following is directly selected Figure 2 The CT X-ray tube shown uses an insulating ceramic-sealed lead assembly as the test carrier, and the entire assembly is brazed at high temperature using pure copper solder, strictly following the grouping process described above. After the sealing and cooling, a helium mass spectrometer is used to perform helium-spray leak testing on each group of products to compare and verify the ability of different barrier layer processes to resist copper melt erosion and maintain the vacuum sealing requirements (i.e., extremely low leakage rate) of the actual product.
[0065] Furthermore, Figure 2The test platform shown is the CT X-ray tube insulating ceramic-sealed lead assembly, which has an extremely demanding structure in actual production. This assembly integrates several typical complex sealing methods in a single product, specifically including: 1) a sleeve seal between the alumina ceramic and the Kovar alloy component (sleeve seal); 2) a pinhole seal between the Kovar alloy component and the nickel needle (pin seal); and 3) a flat seal between the alumina ceramic and the Kovar alloy component (flat seal). The advantage of this test structure is that it can simultaneously and comprehensively evaluate the corrosion resistance and airtight sealing performance of pure copper high-temperature solder and the thickened Ni layer 6 of this invention under different geometric configurations, material combinations, and complex interface thermal stress distributions on a single test assembly. This highly replicates and verifies the practical application potential of this invention under complex assembly conditions of CT X-ray tubes.
[0066] High-temperature service life test: The insulating ceramic-sealed lead assembly and the tensile strength test sample were placed in a vacuum furnace with a maximum temperature of 600℃ and rotated with the furnace to undergo alternating hot and cold cycles. After a certain number of cycles, the tensile strength and airtightness were tested. As shown in Table 5.
[0067] The thickness changes of the molybdenum and nickel layers before and after sealing were measured using an X-ray thickness gauge. The results are shown in Table 2. Table 2. Changes in metallization layer thickness before and after sealing.
[0068] The tensile strength test and airtightness test data are shown in Table 3 below: Table 3 Summary of tensile strength and airtightness test results for different samples
[0069] Table 4 Summary of tensile values for samples #1 and #5
[0070] Table 5. Summary of tensile strength and airtightness of samples #1 and #5 after 600℃ vacuum furnace thermal cycling.
[0071] 4. Test Result Analysis 1) Mechanism of action and airtightness analysis of the barrier layer The test data in Tables 2 and 3 show that the key to effectively preventing the erosion of liquid pure copper lies in the synergistic effect of the "double-layer thickened structure" and the "high-temperature pre-diffusion densification treatment," neither of which can be omitted.
[0072] The necessity of high-temperature densification: Under the premise of the same nickel layer thickness, in Example 1, which underwent high-temperature pre-diffusion treatment, only the loose outer Ni layer 5 was consumed by the copper liquid as a sacrificial layer, while the dense inner Ni layer 4 remained intact; while in Comparative Example 2, which was not treated at high temperature, the entire Ni layer 6 had a loose structure and was completely melted by liquid pure copper and penetrated to the underlying Mo-Mn base metallization layer 2.
[0073] The necessity of increasing the thickness: Although the No. 3 comparative sample also underwent high-temperature pre-diffusion treatment, due to the lack of a double-layer thickening design (the barrier layer was too thin), its physical barrier margin was insufficient, and it was eventually penetrated by the copper liquid.
[0074] All comparative samples that were penetrated by molten copper exhibited lower tensile strength and poorer vacuum tightness. In contrast, Example #1, thanks to this synergistic effect, perfectly resisted pure copper corrosion, demonstrating the highest sealing strength and best vacuum tightness.
[0075] 2) Analysis of sealing strength and fracture morphology The tensile cross-sections of the #1 pure copper brazing example and the #5 conventional AgCu28 brazing example are as follows: Figure 3 As shown, the cross-section is located in the ceramic body region below the basic Mo-Mn metallization layer. Combined with the mechanical test data in Table 4, it can be concluded that: Strength and stability advantages: The components using pure copper brazing filler metal and the thickened barrier layer process of this invention have tensile strength similar to that of traditional AgCu28 silver-copper brazing assemblies, with an average tensile strength that is 4.26% lower. Furthermore, the test data exhibits lower dispersion and smaller fluctuation range, demonstrating excellent process consistency and stability.
[0076] Advantages of the fracture failure mode: In Example 1, the tensile fracture occurred within the ceramic matrix near the interface (i.e., the typical "pulling out" phenomenon / white porcelain area). This failure mode indicates that the metallurgical bonding strength of the ceramic-metal interface exceeds the cohesive fracture strength of 95% alumina ceramic material itself, fully demonstrating that the sealing component of this invention has extremely excellent and reliable interface connection quality.
[0077] High-temperature performance and lifespan advantages: According to the test data in Table 5, after 200 cycles at 600℃, the tensile strength of the product sealed with pure copper solder decreased by 6.1%, while the airtightness still reached 7.6×10⁻⁶. -13 The product sealed with AgCu28 solder showed a 67.9% decrease in tensile strength and a mere 7.6 × 10⁻⁶ after 200 cycles at 600°C. -7 This fully demonstrates that the sealing assembly of the present invention has an extremely excellent high-temperature service life.
[0078] In summary, this invention has the following significant advantages: 1) It solves the erosion problem of high-temperature brazing of pure copper, achieving extremely high sealing strength; by constructing a double-layer thickened Ni layer 6 with "dense inside and loose outside" and supplementing it with high-temperature pre-diffusion densification treatment, this invention fundamentally cuts off the excessive erosion channel of liquid pure copper on the Mo-Mn basic metallization layer 2. Quantitative test results show that after using this process, the tensile strength of the ceramic-metal interface reaches as high as 375.5 MPa, and the leak detection rate of helium mass spectrometry reaches 10%. -13 Pa·m 3 1) Achieving an extremely high vacuum sealing level of / s. 2) Significantly improving the high-temperature service life and operational reliability of components; Unlike traditional medium-temperature silver-copper solders (such as the AgCu28 system), the pure copper solder successfully applied in this invention has a higher melting point and superior thermal conductivity. Benefiting from the inherent material physical advantages of the pure copper system, and combined with the high-strength, corrosion-resistant Ni-Mo interface pre-constructed in this invention, the final sealing assembly is more thermodynamically and structurally stable, thereby effectively improving the service life and reliability of CT tubes under extreme conditions such as long-term high temperature and high heat load. 3) Suitable for complex assembly conditions and possessing high industry promotion value; This invention directly uses ceramic-sealed lead wire assemblies for CT tubes with complex configurations including needle seals and sleeve seals for prototyping and verification, fully demonstrating that this process can overcome the severe challenges brought by different geometric configurations, multiple material combinations, and residual thermal stress at complex interfaces in one go. Its technical solution not only perfectly solves the assembly problem of ceramic-sealed leads, but can also be widely applied to other ceramic-metal sealing assemblies in CT tubes under high temperature and high vacuum conditions, possessing extremely high industrial practical value.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A ceramic-metal sealing structure for inhibiting copper solder erosion, characterized in that, include: Alumina ceramic parts (1); Mo-Mn basic metallization layer (2) formed on the surface of the area to be sealed of the alumina ceramic part (1); Ni layer (6) formed on the surface of the Mo-Mn base metallization layer (2); The Ni layer (6) is divided into an inner dense Ni layer (4) and an outer loose Ni layer (5) in the thickness direction. The dense Ni layer (4) and the Mo-Mn basic metallization layer (2) are bonded together by a high-temperature pre-diffusion treatment to form a Ni-Mo metallurgical bonding layer (3). The loose Ni layer (5) on the outside is used as a sacrificial layer to preferentially react with liquid pure copper and be consumed during the high-temperature brazing of pure copper. The dense Ni layer (4) on the inner side serves as a physical barrier to prevent liquid pure copper from penetrating into the Mo-Mn base metallization layer (2) after the loose Ni layer (5) on the outer side is consumed.
2. The ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 1, characterized in that, The total thickness of the Ni layer (6) is 7~20μm; the thickness of the dense Ni layer (4) is 2~5μm; and the thickness of the loose Ni layer (5) is 5~15μm.
3. The ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 1, characterized in that, The alumina ceramic component (1) is selected from 95% alumina ceramic, 96% alumina ceramic, 99% alumina ceramic, 99.5% alumina ceramic or 99.7% alumina ceramic.
4. The ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 1, characterized in that, The thickness of the Mo-Mn basic metallization layer (2) is 15~25μm.
5. The ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 1, characterized in that, For pure copper brazing, oxygen-free copper TU0, TU1 or TU2 is used as the brazing material, and the brazing temperature for pure copper brazing is 1130~1180℃.
6. A process for preparing a ceramic-metal sealing structure that inhibits copper solder erosion, characterized in that, Includes the following steps: A Mo-Mn-based metallization layer (2) is prepared on the surface of the area to be sealed in the alumina ceramic part (1). A Ni layer (6) is prepared on the surface of the Mo-Mn base metallization layer (2). The Ni layer (6) is divided into an inner dense Ni layer (4) and an outer loose Ni layer (5) in the thickness direction. The alumina ceramic part (1) with Ni layer (6) is placed in a reducing atmosphere furnace for high-temperature pre-diffusion treatment, so that Ni-Mo metallurgical bonding layer (3) is formed between the dense Ni layer (4) and the Mo-Mn basic metallization layer (2). After the pre-diffusion treated alumina ceramic parts (1), pure copper brazing filler metal and metal parts are assembled in a set order, they are subjected to high-temperature vacuum brazing. During the brazing process, the loose Ni layer (5) on the outside is consumed as a sacrificial layer and reacts preferentially with liquid pure copper. The dense Ni layer (4) on the inside acts as a physical barrier to prevent liquid pure copper from penetrating into the Mo-Mn base metallization layer (2).
7. The preparation process of the ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 6, characterized in that, The Ni layer (6) is prepared by any one of electroplating, electroless plating, physical vapor deposition or composite deposition.
8. The preparation process of the ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 7, characterized in that, When using the Ni electroplating process, a two-stage variable current method is employed, specifically including: First-stage electroplating: control the electroplating current density to be 0.5~1.5A / dm² 2 The electroplating time is 15~30min to form a dense Ni layer on the inner side, with a thickness controlled at 2~5μm; Second-stage electroplating: Control the electroplating current density to increase to 4.0~8.0 A / dm² 2 The electroplating time is 3~10min, and the outer loose Ni layer is formed on the surface of the inner dense Ni layer, with the thickness controlled at 5~15μm.
9. The preparation process of the ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 6, characterized in that, The high-temperature pre-diffusion treatment is carried out at a temperature of 750~1050℃ for a time of 20~45min; the reducing atmosphere furnace is a hydrogen furnace or an ammonia decomposition furnace.
10. The preparation process of the ceramic-metal sealing structure for inhibiting copper solder erosion according to claim 6, characterized in that, The high-temperature vacuum brazing temperature is 1130~1180℃, the holding time is 3~20min, and the vacuum degree is below 10. -3 Pa; the pure copper brazing filler metal is selected from oxygen-free copper TU0, TU1 or TU2; the material of the metal parts is selected from any one of Kovar alloy 4J29, Kovar alloy 4J33, Fe-Ni-Co alloy, Fe-Ni alloy, Hastelloy alloy and stainless steel parts with Ni surface plating.
Citation Information
Patent Citations
A sealing solder for vacuum electronic devices and its preparation method
CN108161274B
A method for fabricating a ceramic-metal butterfly-shaped package connector with high tensile strength and high hermeticity.
CN115974575B